A proposed method for reduction of induced zero-sequence current in cable system - Shimaa Abdel-Raouf Salem; Rabab Reda Eiada; Ebrahim Abdel-Ghafar Badran (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Zero-sequence circulating currents are particularly problematic because they can occasionally lead to protective relay failure. However, it is not usually understood that systems with numerous cables strung along the same path will produce zero-sequence currents. In this paper, the operation of parallel connections of single core underground cables is examined. The examination is based on power cables arrangement operating in parallel two-circuit with and without the transmission grid. It was found that symmetrical cable arrangement might significantly lower zero-sequence currents in a twin-circuit. On the other hand, the largest value of the zero sequence currents at asymmetrical configuration. To provide an effective method about reduction of zero sequence current induced in a cable system, several connection scenarios such as the transposition of the cable and sheath and the application of sheath cross bonding are examined. Therefore, in this paper, this phenomenon will be analyzed and discussed. ATPDraw is used to simulate and analysis this kind of study. Also, the effect of sheath transposition is explained and analyzed.